(untitled) (Research, Society and Development, 2024)
Introduction: Ministry of Health data demonstrate that gestational hypertensive disorders have an incidence of 1 to 4% of pregnancies, being the main cause of maternal morbidity and mortality. Regarding heart diseases, the rate of pregnant women affected reaches 4.2%, eight times higher than the international average. Objectives: To study the epidemiological profile of pregnant women admitted to a high-risk maternity ward with gestational hypertensive disorders and/or congenital or acquired heart diseases and analyze possible favorable and unfavorable predictors of maternal and newborn risk. Methods: From January 2022 to June 2023, 282 medical records of pregnant women admitted to Nossa Senhora de Lourdes Maternity Hospital, Aracaju, Sergipe, with a diagnosis of gestational hypertensive syndrome (GHS) and congenital or acquired heart diseases accompanied by obstetrics and cardiology services of the institution were evaluated. A quantitative, descriptive, retrospective, and documentary study was conducted. Results: Of the 282 medical records evaluated, the median age of pregnant women was 30 [IQR 24-36] years. The median gestational age was 37 [IQR 33-38] weeks. Cesarean section (69.1%) was the prevalent delivery method. It was observed that 79.4% of patients had GHS, and 34% had some type of heart disease. There was one maternal death (0.3%) and 13 (4.6%) newborn deaths. The prevalent pathology associated with newborn deaths was GHS. Conclusion: After this epidemiological analysis, a low maternal mortality rate is evident, highlighting the importance of the cardio-obstetric team and the need for improvement in records and workflows.